"Littered with Logos!": An Investigation into the Relationship between Water Provision, Humanitarian Branding, Donor Accountability, and Self-Reliance in Ugandan Refugee Settlements. (18th October 2021) - Martin, Diana; Brown, Julia
Abstract: The branding of humanitarian assets and programme signage (often in English) is common practice in displacement contexts. Such visibility is a reminder of the special status of refugee spaces and a requirement imposed by donors. However, such branding, which forms part of the humanitarian organisations' accountability to donors, raises profound issues in relation to the Comprehensive Refugee Response Framework (CRRF) and the agenda of refugee self-reliance. Drawing on our work on water access in Ugandan refugee settlements for humanitarian NGOs, we present a case study that explores the humanitarian response and its implications on the sustainability of water provision through the lens of branding and accountability. As donors and taxpayers become the (distant) audiences of visibility strategies, we argue that the branding of water structures, coupled with the lack of accountability to affected populations (AAPs) potentially undermines refugees' sense of ownership necessary for the future upkeep and maintenance of water sources. The sector may thus compromise the sustainability of programming as advanced by the CRRF. As accountability to donors is prioritised over AAP, we argue that the impact of branding on sustainability of water provision can be better understood by investigating its psychological effects on programme beneficiaries.